EFFICIENT USE OF V&V TECHNIQUES FOR QUALITY AND CREDIBILITY ASSURANCE OF COMPLEX MODELING AND SIMULATION (M&S) APPLICATIONS - Lehmann, Axel Hans; Wang, Zhongshi (International Journal of Industrial Engineering: Theory, Applications and Practice, 2017)
Due to the increasing complexity and variety of M&S methods, tools and applications, quality control of model design and simulation development (M&S) as well as assurance of credibility and utility of goal oriented M&S applications are becoming more and more challenging. Facing these perspectives and demands, standards, guidelines and techniques for verification, validation and accreditation (VV&A) of M&S have been developed over past decades. Most of these VV&A processes, as well as related V&V techniques are directed to typical M&S application scenarios and their respective acceptability criteria. But concrete methods for risk-cost-benefit calculations as basis for tailoring of VV&A activities according to specific project requirements are almost unknown. Besides a brief summary of state-of-the-art, this paper focuses on experiences applying existing guidelines and standards for VV&A for M&S quality assessment, as well as on challenges arising from increasing complexity and diversity of M&S applications.